Perceived Value, Corporate Image, and Service Quality: An Empirical Study in the Airline Sector (Third Sector Social Economic Review, 2026)
The aim of this study is to examine the perception of service quality at Turkish Airlines and the mediating role of corporate image in this process. To this end, 593 datasets were collected through online and face-to-face surveys. The obtained data were initially analyzed using Exploratory Factor Analysis (EFA). Subsequently, Measurement Model Analysis and Structural Equation Modeling (PLS-SEM) were performed using SmartPLS software to test the research hypotheses. Following these analyses, the hypotheses derived from the existing literature were evaluated using a bootstrapping technique. The findings reveal that the perceived value of Turkish Airlines' flight services does not have a direct effect on perceived service quality. Instead, perceived value significantly influences corporate image, which in turn affects perceived service quality. Furthermore, the mediation analysis demonstrates that corporate image fully mediates the relationship between perceived value and perceived service quality. These results indicate that perceived value does not directly translate into service quality perceptions; rather, corporate image serves as a critical antecedent in this process. This phenomenon suggests that the provided service may not fully align with passenger expectations, potentially due to high ticket prices or service inadequacies. Consequently, it is imperative for Turkish Airlines to comprehensively re-evaluate its cabin crew's service delivery and identify the underlying causes through systematic mystery shopping audits.
Keywords: Perceived Value; Service Quality; Corporate Image; Turkish Airlines; structural equality